(untitled) (Studia Prawnicze / The Legal Studies, 2013)
The paper offers a comprehensive analysis of the monitoring mechanism of the UN Convention on the Rights of Persons with Disabilities adopted in 2006. It presents the structure of the Committee on the Rights of Persons withm Disabilities which monitors implementation of the treaty by the States Parties and its monitoring tools, i.e. mandate to examine reports of the States Parties, to consider individual communications and to conduct inquiries. It indicates that, even though the monitoring mechanism of the Convention on the Rights of Persons with Disabilities is based foremost on elements typical for other, more embedded UN human rights treaty bodies, it also owns its specific, innovative characteristics. These novelties are related to the particular needs of beneficiaries of the treaty and attempts to improve the monitoring procedures.